Determinación de los costos de calidad del procesamiento de almidón en la microempresa “YUCA PAN” de la ciudad de Calceta - González Morales, Martha Valentina (2023)
The development of this research aimed to determine the costs associated with the quality of starch processing in the microenterprise “Yuca Pan” in Calceta city as a contribution to the optimization of its resources, in order to identify those elements of the processes that represent a higher level of costs and in which the delays inherent in the production are associated with a greater risk of damage to the product, affecting its quality. To achieve the final purpose of the research, the theoretical and methodological bases were used to identify the costs of non-quality. Similar research was taken as a reference point that allowed the application of previously validated quantitative tools. Once the information was obtained, it was determined that an effective decision should directly reduce the costs of the demand for poor quality of the process. A bibliographic review of the selected topics was carried out and the most representative factors causing higher costs considered to be of low quality were identified. Within the determination of the methodology, the need to apply primary information collection methods such as observation sheets and interviews was established. In conclusion, it can be stated that the multiplicity of processes, procedures and standards in healthy companies is very important, that the organization has methods to quantify failures, errors and repetitions and therefore has an objective basis for decision making.